Structural equation model and effect of brain breaks video exercise on transtheoretical constructs and physical activity among people with type 2 diabetes mellitus - Hidrus, Aizuddin (2021)
Physical activity (PA) has become a cornerstone in developing and maintaining a healthy lifestyle over the past century. A high percentage of people with type 2 diabetes mellitus (T2DM) are physically inactive. Many theoretical instruments have been developed to study the psychological mechanism behind people’s attitudes towards PA. The transtheoretical model (TTM) is a cohesive model and was developed to encourage changes in a person’s behaviour when they felt ready to change. TTM that consists of Stages of change (SOC), Processes of change (POC), Decisional balance (DB), and Self-efficacy (SE) were commonly applied to assess a person's preparedness to adopt a new, healthier habit and offers suggestions, or change processes, to help them. Motivation is one of the essential components in the psychological process of individuals in deciding their participation in physical activities. There were two main objectives of this study. First, to determine the relationship between TTM psychological constructs, motives for PA and amount of PA among people with T2DM at Hospital Universiti Sains Malaysia (USM), Kelantan. While second objective, to identify the effect of Brain Breaks video intervention on the measured variables among people with T2DM at Hospital USM. The study was carried out in two phases, which were phase 1, a cross-sectional study and phase 2, a randomised controlled trial. Purposive sampling was used to recruit participants. In phase 1, 331 people with T2DM were recruited, and 70 people from phase 1 were involved in phase 2. The TTM,physical activity and leisure motivation scale (PALMS), and international physical activity questionnaire (IPAQ) were used to measure the behaviour changes and motivation for and the amount of PA. Participants in phase 1 completed a set of questionnaires, consists of the demographics data, TTM [processes of change (POC) scales, decisional balance (DB) scales, exercise self-efficacy (ESE) scales], PALMS, and IPAQ. After the level of participants’ POC, DB, ESE, PA motivation, and PA amount were determined, Phase 2 was performed to discover the effectiveness of video intervention on the measured variables. Participants in phase 2 were randomised into intervention and control groups who underwent four months of intervention. A10-minutes Brain Breaks video featuring exercises were given only to the intervention group. Both groups completed the same set of questionnaires monthly until the fourth month of the intervention period. The collected data were analysed with SPSS 26 for descriptive statistics, graphs, and repeated measures analysis of variance and repeated measures multivariate analysis of variance and Mplus 8 for confirmatory factor analysis and structural equation modelling. In phase 1, most participants were males (52%) and Malays (89.4%) with a mean age of 62.6 years (SD 0.56). The final structural model fits the data well as it produced good model fit indices [comparative fit index (CFI) = 0.953, Tucker Lewis index (TLI) = 0.925, standardised root mean square residual (SRMR) = 0.031, root mean square error of approximation (RMSEA) (90% CI) = 0.059 (0.040, 0.078), RMSEA p-value = 0.209]. It also produced a significant inter-relationship between the TTM, PA motives and amount of PA, with 16 SEM specific hypotheses (11 hypotheses from the initial model and five additional alternative hypotheses) were supported by the final model. Pros of DB, other’s expectation, and psychological condition were constructs that directly affected PA, while the other constructs had a significant indirect relationship with PA. As in phase 1, participants inphase 2 were also predominantly Malays (90%) and males (55.7%), with a median age was 56 years (IQR = 10). The intervention group showed significantly higher score than the control group in nine psychological constructs [cognitive, behavioural, pros, cons, appearance, others’ expectation, physical condition, mastery, and ESE with p-values < 0.001, < 0.001, < 0.001, 0.008, 0.014, < 0.001, 0.023, 0.021, and < 0.001, respectively]. The intervention group also scored significantly higher in the amount of PA than the control group (p-value = 0.001). In conclusion, a positive mind-set is crucial in deciding a behavioural change towards an active lifestyle in people with T2DM, because it influences POC, DB, ESE and PA motivations with PA performance. Brain Breaks videos empirically beneficial for people with T2DM because they changed people’s behaviour and motivations to make them inclined towards more PA.